2019
DOI: 10.4081/or.2019.7948
|View full text |Cite
|
Sign up to set email alerts
|

Is subscapularis repair correlated with better outcome compared to non-repair in reverse total shoulder arthroplasty? A systematic review of comparative trials

Abstract: We aimed to investigate whether combined reverse total shoulder arthroplasty (RTSA) and subscapularis repair leads to improved clinical and functional outcome in comparison with RTSA alone. Two reviewers independently conducted a systematic search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) using the MEDLINE/PubMed database and the Cochrane Database of Systematic Reviews. These databases were queried with the terms “reverse” AND “shoulder” AND “arthroplasty” AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Only retrospective or non-randomized studies existed prior to our study [6,10,11,13,14,23,24]. Malahias et al [23] did a review of the most common (retrospective) studies on this question [6,10,11,13,14], focusing on functional outcomes and dislocation rates after rTSA. They concluded that a…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only retrospective or non-randomized studies existed prior to our study [6,10,11,13,14,23,24]. Malahias et al [23] did a review of the most common (retrospective) studies on this question [6,10,11,13,14], focusing on functional outcomes and dislocation rates after rTSA. They concluded that a…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first prospective-randomized trial analyzing the management of the SSC-tendon in primary rTSA. Only retrospective or non-randomized studies existed prior to our study [ 6 , 10 , 11 , 13 , 14 , 23 , 24 ]. Malahias et al [ 23 ] did a review of the most common (retrospective) studies on this question [ 6 , 10 , 11 , 13 , 14 ], focusing on functional outcomes and dislocation rates after rTSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse total shoulder arthroplasty (rTSA) is a surgical technique that was approved for use in the United States in the early 2000's 15 . The prosthetic design compensates rotator cuff deficiency through medialization of the glenohumeral region such that the deltoid functions to both elevate and abduct the glenohumeral joint 12 . While the prosthesis utility has expanded to address a various glenohumeral bony pathologies and cases of severe chronic instability 5 , management of the subscapularis tendon during rTSA remains a topic of debate.…”
Section: Level Of Evidence: Level Iv; Systematic Reviewmentioning
confidence: 99%
“…17,18 The subscapularis tendon Biomechanic and functional implications of subscapularis tendon repair have been investigated thoroughly in patients treated with reverse total shoulder arthroplasty. [18][19][20] Whether to repair the subscapularis tendon or not remains an interesting topic in the field of reverse total shoulder arthroplasty. Friedman et al reported excellent outcomes after RTSA for both patients with and without subscapularis repair with a follow-up comparable to this present study.…”
Section: Functional Scoresmentioning
confidence: 99%